Croatia Country Report - Siniša, Rodin (2000)
Popular sovereignty in Croatia can be exercised either by representation, or by direct democracy, i.e. by direct popular involvement in decision making. Following initial overview of legal rules regulating exercise of direct democracy in Croatia, it will be demonstrated that almost complete absence of national referenda over the past eight years of Croatia's independence can be explained by specific political consensus among the President of the Republic, the Parliamentary majority and the Government. I will also present relevant decisions of the Constitutional Court on the point and try to answer to what extent probability of referenda in Croatia depends on institutional balance.